2017
DOI: 10.1039/c6ra26700a
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric chemical reaction mechanism and kinetics of 1,2-bis(2,4,6-tribromophenoxy)ethane initiated by OH radical: a computational study

Abstract: The mechanism and kinetics of OH-initiated oxidation of BTBPE, an alternative of PBDEs, were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
(74 reference statements)
0
15
0
Order By: Relevance
“…Reactants and transition states may have multiple conformers. Previous studies found that the involvement of multiconformers can more precisely predict the reaction kinetics, compared to single-conformer approximation. ,,, A so-called single-conformer approximation implies that only one conformer for reactant and transition state was used in studying reaction mechanism and kinetics. ,,,,, , Here, multiconformer approximation was considered in the crucial reaction steps. The crucial reaction steps are determined by a kinetics analysis based on single-conformer approximation (details in the SI).…”
Section: Introductionmentioning
confidence: 99%
“…Reactants and transition states may have multiple conformers. Previous studies found that the involvement of multiconformers can more precisely predict the reaction kinetics, compared to single-conformer approximation. ,,, A so-called single-conformer approximation implies that only one conformer for reactant and transition state was used in studying reaction mechanism and kinetics. ,,,,, , Here, multiconformer approximation was considered in the crucial reaction steps. The crucial reaction steps are determined by a kinetics analysis based on single-conformer approximation (details in the SI).…”
Section: Introductionmentioning
confidence: 99%
“…Density functional theory (DFT) methods represent a viable alternative for elucidating the kinetics and mechanisms of atmospheric chemistry processes, due to their excellent performance‐to‐cost ratio . Thus far, many functionals have been developed, each with merits and drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…• OH addition reactions play a pivotal role in the atmospheric transformation of a number of phenyl and substituted phenyl‐based persistent and toxic organic pollutants, such as polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), and polybrominated diphenyl ethers (PBDEs) . Consequently, the mechanisms and rate constants ( k OH ) of atmospheric • OH addition reactions are of great significance to determining their environmental risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Previous studies had revealed that the estimated OH values of some compounds by AOPWIN beyond its domain were significantly lower than the calculated values quantum chemical methods. 11,40 This suggested that the potential risk of LCMs in atmosphere might be underestimated. Therefore, in order to accurately assess the fate and transport of LCMs in the atmosphere, it is better to investigate their transformation kinetics rather than using the AOPWIN modeled gaseous kinetics.…”
Section: ■ Results and Discussionmentioning
confidence: 99%